2019
DOI: 10.1039/c9ra00008a
|View full text |Cite
|
Sign up to set email alerts
|

AlN epitaxy on SiC by low-temperature atomic layer deposition via layer-by-layer, in situ atomic layer annealing

Abstract: The schematic diagram of the processing cycle including the atomic layer annealing (ALA) to achieve low-temperature epitaxial growth of AlN on SiC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In fact, in situ atomic layer-by-layer annealing has been first applied to the PEALD of III-nitride family materials (AlN and GaN), where it enabled highly crystalline epitaxial film growth on sapphire and SiC substrates at relatively reduced temperatures as low as 300 °C. , Additionally, it has been also shown that layer-by-layer in situ plasma treatment significantly improves the dielectric properties of oxide based high- k gate dielectric materials (HfO 2 and ZrO 2 ) by enhancing the crystallinity of such layers. There have been mainly two proposed mechanisms taking place during the atomic layer plasma annealing that leads to the film crystallinity improvement and thus bulk properties: (i) a process termed “surface crystallization”, where each deposited film layer absorbs energy from the highly energetic plasma-generated ions and radicals (during in situ Ar plasma) promoting adatom migration, that is, surface adatoms will gain extra energy, enabling them to find more suitable arrangements/sites and thus result in layer crystallization; (ii) a second process named “surface heating”, during which the absorbed energy from the plasma (Ar plasma) increases the surface temperature within a few monolayers (∼5 monolayer in the AlN case) which enhances the reactivity of the following precursor dose resulting in more efficient ligand desorption/removal as well as facilitating surface adatom migration . We believe that similar mechanisms are taking place during our in situ Ar plasma annealing incorporated gallium oxide growth recipes, which enabled to achieve as-grown crystalline β-Ga 2 O 3 films on Si, sapphire, and amorphous glass at substrate temperatures as low as 200 °C.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In fact, in situ atomic layer-by-layer annealing has been first applied to the PEALD of III-nitride family materials (AlN and GaN), where it enabled highly crystalline epitaxial film growth on sapphire and SiC substrates at relatively reduced temperatures as low as 300 °C. , Additionally, it has been also shown that layer-by-layer in situ plasma treatment significantly improves the dielectric properties of oxide based high- k gate dielectric materials (HfO 2 and ZrO 2 ) by enhancing the crystallinity of such layers. There have been mainly two proposed mechanisms taking place during the atomic layer plasma annealing that leads to the film crystallinity improvement and thus bulk properties: (i) a process termed “surface crystallization”, where each deposited film layer absorbs energy from the highly energetic plasma-generated ions and radicals (during in situ Ar plasma) promoting adatom migration, that is, surface adatoms will gain extra energy, enabling them to find more suitable arrangements/sites and thus result in layer crystallization; (ii) a second process named “surface heating”, during which the absorbed energy from the plasma (Ar plasma) increases the surface temperature within a few monolayers (∼5 monolayer in the AlN case) which enhances the reactivity of the following precursor dose resulting in more efficient ligand desorption/removal as well as facilitating surface adatom migration . We believe that similar mechanisms are taking place during our in situ Ar plasma annealing incorporated gallium oxide growth recipes, which enabled to achieve as-grown crystalline β-Ga 2 O 3 films on Si, sapphire, and amorphous glass at substrate temperatures as low as 200 °C.…”
Section: Results and Discussionmentioning
confidence: 99%
“…By changing the inert gas from Ne (∼20 amu) to Ar (∼40 amu) or Kr (∼80 amu), while maintaining constant ion current density and treatment time, momentum could independently be tuned from energy and flux. If the primary crystallization effect was due to a plasma heating effect, it was expected that the crystallization effect would be independent of inert ion mass, or as noted in previous reports, 16,21 that heavier ions would reduce the crystalline quality of the film by inducing ion damage. 18,22…”
Section: Resultsmentioning
confidence: 86%
“…In the present report, the mechanism of the ALA process is elucidated using AlN as an example material system due to its wide-ranging applications for crystalline films as a heat spreader or piezoelectric material. It was previously reported that ALA strongly relies on a so-called surface heating effect; 7,16,18,20 however, through systematic experimental variation of inert ion mass, plasma delay time, and molecular dynamics (MD) simulations, it is shown that the process is most consistent with a momentum transfer process resulting in effective local thermal excitation leading to surface crystallization (See schematic of ALA AlN process in Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we have proposed the atomic layer annealing (ALA) technique to significantly improve the electrical characteristics of ferroelectric and high-K gate dielectrics, 27,28 as well as the epitaxial quality of III–V nitride semiconductors. 29,30 ALA is an in situ , layer-by-layer plasma treatment introduced in the ALD cycle to facilitate adatom migration, thereby improving the material quality of nanoscale thin films. The ALA process has also been used to suppress the number of nitrogen vacancies in the AlN surface passivation layer, which significantly reduces the leakage current and enhances the reliability of Ge-based metal-oxide-semiconductor devices.…”
Section: Introductionmentioning
confidence: 99%